High-entropy alloy CoCrFeMnNi produced by powder metallurgy. (27th May 2017) - Eißmann, Nadine; Klöden, Burghardt; Weißgärber, Thomas; Kieback, Bernd
ABSTRACT: Lately high-entropy alloys (HEAs) have been the topic of extensive research, as these materials are promising candidates for many challenging applications, as for example tools, moulds and functional coatings. In contrast to conventional alloys, HEAs consist of five or more principal elements, each having a concentration between 5 and 35 at.-%. Against expectations, HEAs show a rather simple microstructure consisting preferentially of cubic phases. Due to this microstructure, HEAs show promising properties, e.g. in terms of high-temperature stability, high strength and ductility. Within this research, a single-phase CoCrFeMnNi HEA was produced by powder metallurgy (PM). In contrast to conventional metallurgy, PM offers a lot of advantages, e.g. good material efficiency and high shape complexity. Gas atomised powder was used and selected PM methods are presented (e.g. pressureless sintering, spark plasma sintering, additive manufacturing (EBM)). The process methods were evaluated by characterising the material properties (density, microstructure, mechanical properties) of the compacted and sintered samples.